Language Aspects of 2 Years 11 Months Old Children: Psycholinguistic Study - Uliana Hidayatika; Dona Aji Karunia Putra (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
The kidsfluencer phenomenon is increasingly popular in Indonesia, supported by children's advanced language abilities “play a key role in the acquisition process” in language. The main problem in this research relates to understanding children's language acquisition at that age, which is often considered limited to simple words. This study aims to describe the language aspects of a kidsfluencer aged 2 years 11 months through a psycholinguistic approach and examine the supporting factors in the language acquisition process. This research was conducted using a qualitative approach with a descriptive method. The data in this research is in the form of utterances produced by a kidfluencer aged 2 years and 11 months. The data collection techniques applied in this research include documentation, observation, and note-taking. Data analysis was carried out in 3 stages, namely 1) reduction, 2) presentation, and 3) conclusion. The results show that children at this age can compose sentences with clear structures and understand and respond to more complex verbal instructions. This research also reveals the important role of rich verbal interaction in supporting children's language acquisition. The conclusion drawn from this study is that children's language abilities at 2 years and 11 months are more developed than expected, and social interaction and a supportive verbal environment are instrumental in the process.